Politics, Power, Poverty and Global Health: Systems and Frames - Solomon Benatar (Kerman University of Medical Sciences, 2016)
Striking disparities in access to healthcare and in health outcomes are major characteristics of health across the globe. This inequitable state of global health and how it could be improved has become a highly popularized field of academic study. In a series of articles in this journal the roles of power and politics in global health have been addressed in considerable detail. Three points are added here to this debate. The first is consideration of how the use of definitions and common terms, for example 'poverty eradication,' can mask full exposure of the extent of rectification required, with consequent failure to understand what poverty eradication should mean, how this could be achieved and that a new definition is called for. Secondly, a criticism is offered of how the term 'global health' is used in a restricted manner to describe activities that focus on an anthropocentric and biomedical conception of health across the world. It is proposed that the discourse on 'global health' should be extended beyond conventional boundaries towards an ecocentric conception of global/planetary health in an increasingly interdependent planet characterised by a multitude of interlinked crises. Finally, it is noted that the paucity of workable strategies towards achieving greater equity in sustainable global health is not so much due to lack of understanding of, or insight into, the invisible dimensions of power, but is rather the outcome of seeking solutions from within belief systems and cognitive biases that cannot offer solutions. Hence the need for a new framing perspective for global health that could reshape our thinking and actions.